(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. The development of education in general and higher education in particular provides funding from the budgets of various levels. According to the law, the state provides allocations for education in the amount of not less than seven percent of GDP from the state, local budgets and other sources of funding not prohibited by law. The purpose of the article is to to form a mechanism of financial and investment support for the development of higher education in Ukraine in the context of the functioning of the European Higher Education Area (EHEA). Results. In 2018, the contributions of the Ministry of Education and Science of Ukraine (44,77 %), households (26,66 %) and regional budgets/local government (12,31 %) were the most significant in general expenditures on higher education. Contributions from other financial agents were less than 10 % of the total. The costs of higher education providers were as follows: services in the field of education – 91,47 %; secondary activities within educational institutions – 3,67 %; secondary activities related to education – 4,85 %. The formed mechanism of financial and investment support for the development of higher education in Ukraine in the context of the EHEA includes financial agents (Central Government, regional budgets/local government, non-governmental sector), tools and relevant measures at the macro-, meso- and microlevels. Conclusions. Recommendations for improving the financial and investment support for the development of higher education in terms of income (diversification of sources of funding for higher education institutions (HEIs) with increasing the share of regional and local budgets; intensification of work with various funds, centers, donors and philanthropists; revival of own investment activity; diversification of products (goods, works, services)) and expenditures (reduction in the total share of consumption expenditures that ensure the current functioning of the HEIs; increase in the total share of development expenditures for financial support of scientific, investment and innovation activities of the HEIs) are formed